The Effect of Adding Carrot Flour (Daucus carota L) to The Nutritional Value and Organoleptic Snakehead Fish Nuggets (Channa striata) - R Adharyan Islamy; Petrus Senas (Jurnal Penelitian Pendidikan IPA, 2023)
Nuggets are one of the results of fishery diversification as a practical and fast food. The aim of this study to determine the effect of adding carrot flour (Daucus carota L) on the nutritional value and organoleptic of snakehead fish nuggets (Channa striata). The research method used a completely randomized design (CRD) with 4 treatments and 3 replications. The best test results for the nutritional value of snakehead fish nuggets were the Addition of 75 grams of carrot flour to a weight of 500 grams of snakehead fish meat which had a water content of 33.36%, protein content of 25.30%, ash content of 2.45%, fat content of 19.09% and carbohydrate content of 19.79%. The best organoleptic test results were the Addition of 75 grams of carrot flour to a weight of 500 grams of snakehead fish meat based on preference and willingness on the average nugget taste of 5.8, average nugget color 5.8, average nugget aroma 5.9 and average nugget texture 5.9 . The best result of the nugget effectiveness index test was the Addition of 75% carrot flour to the weight of 500 grams of snakehead fish meat with an effectiveness index value of 0.57.